Manajemen Risiko Operasional dalam Perspektif Good Corporate Governance dan Good Public Governance - Karnila, Karnila; Irsyad, Irsyad; Tia Ayu Ningrum (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Operational risk management from the perspective of Good Corporate Governance (GCG) and Good Public Governance (GPG) is a systematic approach that integrates governance principles to identify, assess, and control risks that can disrupt the continuity and effectiveness of organizations, both in the private and public sectors. GCG provides transparent and accountable structures, mechanisms, and controls to minimize the risk of process failure, human error, and system disruptions, thereby ensuring the sustainability of company operations. On the other hand, GPG emphasizes the principles of transparency, accountability, participation, and compliance in managing risks to ensure optimal public services run without serious obstacles. The application of these principles creates a strong risk culture and an effective internal control system, which not only protects assets and reputation but also strengthens public and stakeholder trust in the long term.